The Effect Of Date Fruit Consumption On Hemoglobin Levels In Pregnant Women In Trimester III - Anita Manan; Sri Dinengsih; Jenny Anna Siauta (Universitas Islam Lamongan, 2021)
Pregnancy is a period that is eagerly awaited because this period greatly determines the quality of human resources and the future of the fetus in the womb will greatly determine the development of the child in the future.Purpose: This study aims to determine the effect of consumption of dates on hemoglobin levels in trimester III pregnant women at Kolaka Public Health Center, Kolaka Regency, Southeast Sulawesi Province in 2020.Methodology: This study used a quasi experimental research design. The study population was all pregnant women in the third trimester who experienced anemia in October-December 2020, as many as 22 people at the Kolaka Health Center.Results: There was an effect of hemoglobin levels before and after giving dates in the treatment group (p = 0.000). There was an effect of hemoglobin levels after giving dates between the treatment group and the control group (p = 0.001).Conclusions:There is an effect of hemoglobin before and after giving dates in a group of pregnant women who are given dates and Fe tablets at the Kolaka Health Center, Kolaka Regency, Southeast Sulawesi in 2020.Suggestion: Increase the provision of health education about nutrition, especially anemia to pregnant women in the working area of Puskemas Kolaka and carry out routine Hb level checks in the first and third trimester of pregnancy.